2008
DOI: 10.1007/s00592-008-0062-7
|View full text |Cite
|
Sign up to set email alerts
|

Repaglinide plus single-dose insulin glargine: a safe regimen for low-risk type 2 diabetic patients who insist on fasting in Ramadan

Abstract: Aim of this prospective study is to evaluate the effect of repaglinide t.i.d. (three times a day) plus single-dose insulin glargine regimen in low-risk type 2 diabetic patients during Ramadan fasting. Participants had been taking the regimen for at least 3 months. Patients with a history of diabetic coma, severe hypoglycemic crisis or repeating attacks of hypoglycemia were excluded. Hypoglycemic unawareness, kidney or liver disease or HbA1c over 8% were also accepted as exclusion criteria. Eleven patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 6 publications
1
32
0
1
Order By: Relevance
“…Two smaller observational studies found insulin glargine to be safe to use during Ramadan, with no significant increases in hypoglycaemia when compared with non-fasting individuals or when compared with those taking OADs [26,28].…”
Section: Insulin Treatment For T2dmmentioning
confidence: 99%
See 1 more Smart Citation
“…Two smaller observational studies found insulin glargine to be safe to use during Ramadan, with no significant increases in hypoglycaemia when compared with non-fasting individuals or when compared with those taking OADs [26,28].…”
Section: Insulin Treatment For T2dmmentioning
confidence: 99%
“…In two small observational studies, no hypoglycaemic events were reported in patients treated with repaglinide during Ramadan [26,27]. A third study demonstrated no difference in hypoglycaemia when compared with insulin glargine or glimepiride, a sulphonylurea (SU) therapy [28].…”
Section: Short-acting Insulin Secretagogues (Meglitinides)mentioning
confidence: 99%
“…No significant differences were reported amongst the three phases of the study. The risk of hypoglycaemia did not differ in the sample in the study compared to control and does not show any difference among the three treatment regimens (Bakiner et al, 2009;Cesur et al, 2007).…”
Section: Adjusting the Hypoglycaemic Therapy For Diabetic Patients Dumentioning
confidence: 71%
“…Bakiner et al have reported that a dose of repaglinide taken before the two main meals of the day in addition to a single insulin glargine is safe and it does not provoke hypoglycaemia or changes in body weight in low-risk individuals committing to fasting (Bakiner et al, 2009). …”
Section: Adjusting the Hypoglycaemic Therapy For Diabetic Patients Dumentioning
confidence: 99%
“…The advantages and disadvantages of fasting in patients with type 2 diabetes are still under consideration. Despite the conflicting results of some studies (19), the results show that fasting during Ramadan can lead to increase the risk of hypoglycemia and hyperglycemia in the patients with type 1 and 2 diabetes (2).…”
Section: Discussionmentioning
confidence: 99%